2011
DOI: 10.1159/000335648
|View full text |Cite
|
Sign up to set email alerts
|

Update on Kleefstra Syndrome

Abstract: Kleefstra syndrome is characterized by the core phenotype of developmental delay/intellectual disability, (childhood) hypotonia and distinct facial features. The syndrome can be either caused by a microdeletion in chromosomal region 9q34.3 or by a mutation in the euchromatin histone methyltransferase 1 (EHMT1) gene. Since the early 1990s, 85 patients have been described, of which the majority had a 9q34.3 microdeletion (>85%). So far, no clear genotype-phenotype correlation could be observed by studying the cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
139
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(145 citation statements)
references
References 46 publications
3
139
0
3
Order By: Relevance
“…25 Among patients with this microdeletion, 54% have behavioral and psychiatric problems, 58% demonstrate abnormalities on brain imaging, 36% have a concurrent diagnosis of epilepsy, and 20% are defined as obese.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Among patients with this microdeletion, 54% have behavioral and psychiatric problems, 58% demonstrate abnormalities on brain imaging, 36% have a concurrent diagnosis of epilepsy, and 20% are defined as obese.…”
Section: Discussionmentioning
confidence: 99%
“…25 Characterized by a phenotype of childhood hypotonia, intellectual disability, and distinctive facial features, this syndrome is often accompanied by myriad psychiatric and behavioral disorders. 12,22,25 While deep brain stimulation (DBS) has been used as a treatment for a number of neuropsychiatric conditions including obsessive-compulsive disorder (OCD), depression, and Tourette syndrome (TS), there is no literature on using DBS for the neuropsychiatric symptoms of a purely genetic disorder. In 1999, Nuttin and colleagues 18 were the first to describe the use of DBS for OCD, and their encouraging initial experience was confirmed with additional studies, 8,9,19 resulting in FDA approval of DBS for the treatment of OCD.…”
Section: Neurosurg Focus 38 (6):e12 2015mentioning
confidence: 99%
“…29 Notably, it has been reported that 40-50% of the human patients with EHMT1 haploinsufficiency exhibit an obese phenotype. 34,35 We have shown that adipose-specific deletion of EHMT1 by an Adiponectin-Cre lowers whole-body energy expenditure and causes obesity, hepatic steatosis and insulin resistance under a high-fat diet. These results indicate that EHMT1 is a critical enzyme for whole-body energy homeostasis in rodents and in humans.…”
Section: Genetic Contribution Of Ehmt1 and Energy Homeostasismentioning
confidence: 99%
“…Microdeletions in the telomeric region of the long arm of chromosome 9 were found in patients with Kleefstra syndrome [6,7], whereas microdeletions of the telomeric end of the short arm may lead to 46,XY gonadal dysgenesis [2].…”
Section: Introductionmentioning
confidence: 99%
“…The literature regarding genital malformations in males with the presence of r(9) is very sparse; however the following malformations have previously been reported: cryptorchidism, hypospadias and micropenis [7]. Until now it is not clear whether the presence of r(9) affects spermatogenesis, as most cases have been described in young boys.…”
Section: Introductionmentioning
confidence: 99%